Measuring the heating power of magnetic nanoparticles: an overview of currently used methods. (2017) - Lemal, Philipp; Geers, Christoph; Rothen-Rutishauser, Barbara; Lattuada, Marco; Petri-Fink, Alke
Abstract: Magnetic hyperthermia describes a novel strategy to generate temperatures up to 45-47°C in tumor tissue through the use of magnetic nanoparticles. Measuring the heating power of magnetic nanoparticles is essential to improve therapy systems currently used by maximizing therapeutic efficiency while minimizing administrated dose. This review reports an overview about available measurement set-ups described in literature, addressing advantages and disadvantages, and includes several more recent approaches developed to fulfill the requirements of accurate and reproducible heating power determination.